1993
DOI: 10.1136/sti.69.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of medical students to HIV and AIDS.

Abstract: Objective-To assess the knowledge and attitudes of medical students to HIVIAIDS and whether attitudes correlate with knowledge and clinical experience. To determine if students felt adequately prepared to deal with medical and psychological aspects of HIVIAIDS. Subjects and Methods-The subjects consisted of 190 London and 99 Cambridge medical students at the end of their genitourinary medicine attachment, plus 230 Cambridge medical students at the end of their second pre-clinical year. Between March 1991 and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
1
24
0
2
Order By: Relevance
“…[5][6][7][8] It is also important to understand the current attitudes of medical students who will be the future generation of healthcare providers. [9][10][11][12][13] Modifications of curriculum have been proposed in some medical schools to address the changes in attitudes toward homosexuality. [14][15][16][17] The attitudes among medical students in a predominantly Chinese culture, such as that of Hong Kong, have not been studied.…”
mentioning
confidence: 99%
“…[5][6][7][8] It is also important to understand the current attitudes of medical students who will be the future generation of healthcare providers. [9][10][11][12][13] Modifications of curriculum have been proposed in some medical schools to address the changes in attitudes toward homosexuality. [14][15][16][17] The attitudes among medical students in a predominantly Chinese culture, such as that of Hong Kong, have not been studied.…”
mentioning
confidence: 99%
“…He suggested that medical educators need to convey not only accurate information about HIV, but try to ensure that medical students spend suf® cient time seeing patients with HIV/AIDS during their training. Evans et al 28 concluded in their study of medical students at the end of their GU medicine attachment that the majority of students in the survey did not feel adequately prepared to deal with the medical and psychological problems of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of knowledge about HIV testing, and the problems with anonymity, patients and HCWs alike, even when knowledgeable in HIV treatment and prevention, are often reluctant to get tested for HIV out of fear that positive test results will affect reputations, employment status and insurance benefits. Although previous studies have critically evaluated both patients' and HCWs' perspectives regarding HIV testing and disclosure (see, for example, Dixon-Mueller 2007;Galletly et al 2008;Kagan et al 2008;Tesoriero et al 2008), there are few recent studies examining medical students' perspectives (see e.g., Evans et al 1993). …”
Section: Practice Pointsmentioning
confidence: 99%